Maternal Noninfectious Fever Enhances Cell Proliferation and Microglial Activation in the Neonatal Rat Dentate Gyrus. Issue 1 (March 2020) - Pancaro, C.; Boulanger-Bertolus, J.; Segal, S.; Watson, C.J.; St Charles, I.; Mashour, G.A.; Marchand, J.E.
Abstract : ( Anesth Analg . 2019;128(6):1190–1198) Maternal fever during labor is a complication that poses many risks for the infant being delivered, and is frequently associated with epidural analgesia. Elevated levels of a proinflammatory cytokine called interleukin-6 (IL-6) are found in the maternal serum and umbilical cord blood of patients with fevers who received an epidural. These investigators have demonstrated through previous studies that higher IL-6 levels can cause temperature increases in rats, and are also connected with microglial activation and subventricular inflammation. In addition, the authors have conducted prior research that connected a higher IL-6 measurement to maternal systemic and fetal brain inflammation. This current study aimed to examine the effect of maternally administered IL-6 on neonatal brain development.